PRINSIP TUNTAS SEBAGAI MANIFESTASI KEADILAN DALAM UPAYA REKONSTRUKSI PUTUSAN ATAS GUGATAN TIDAK DAPAT DITERIMA - Samsiati, Samsiati (Judex Laguens, 2024)
To this date, the applicable rules and regulations in Indonesia have not specified the reasons on which a court may declare a lawsuit inadmissible (Niet-Ontvankelijk verklaard). Although there is still a substantial amount of jurisprudence that fills in legal gaps, uniformity has not been attained. This legal void may lead to Niet-Ontvankelijk verklaard contradicting the principle of prompt, simple, low cost, and complete judgment. This study employs legal research with statute approach, conceptual approach, case approach, and comparative approach to examine this issue. This study reaches conclusions: First, the ratio legis of Niet-Ontvankelijk verklaard is intended to permit civil lawsuits that do not meet the legal conditions for a lawsuit to be settled at the outset of the case settlement procedure, without first analyzing the subject matter of the case. Second, it is paramount essential to introduce new provisions in Indonesia's Civil Procedure that regulates: the types and forms of exceptions; rules on the limitation of legal remedies against Niet-Ontvankelijk verklaard; and an active and ex officio affirmation of the judge's authority stating that the lawsuit cannot be accepted, without objection or exception from the defendant, so long as the decision is based on the reasons for the exception.